2016
DOI: 10.1007/5584_2016_221
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Cognition of Mitochondrial Respiratory System Proteins in Peripheral Blood Mononuclear Cells in the Course of Lung Cancer

Abstract: Peripheral blood mononuclear cells (PBMC) represent an easily available population of cells for the studies on remote effects of lung cancer. NADH dehydrogenase (ubiquinone) Fe-S protein-1 (Ndufs1), a marker of mitochondrial complex I, and mitochondrially encoded cytochrome c oxidase 1 (MTCO1), a marker of complex IV, may participate in cognitive decline during the course of lung cancer. In this study, Ndufs1 and MTCO1 expression in PBMC was evaluated by means of ELISA in 80 lung cancer patients. Mini-Mental S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The role of mitochondrial ribosomal protein S23 (MRPS23) in carcinoma cell proliferation could be a potential therapeutic target, in case of interference of hepatocellular cancer proliferation, oncogenesis and metastasis (Pu et al 2017). The expression of COX1 was involved in endometrial cancers (Ksiezakowska-Lakoma et al 2017), esophageal adenocarcinoma (Huhta et al 2017) and lung cancer (Michalak et al 2016). Taken all together, these examples support the notion that mitochondria contribute to the angiogenetic, tumorigenic, proliferation, invasive and metastatic features of cancer cells.…”
Section: Introductionmentioning
confidence: 67%
“…The role of mitochondrial ribosomal protein S23 (MRPS23) in carcinoma cell proliferation could be a potential therapeutic target, in case of interference of hepatocellular cancer proliferation, oncogenesis and metastasis (Pu et al 2017). The expression of COX1 was involved in endometrial cancers (Ksiezakowska-Lakoma et al 2017), esophageal adenocarcinoma (Huhta et al 2017) and lung cancer (Michalak et al 2016). Taken all together, these examples support the notion that mitochondria contribute to the angiogenetic, tumorigenic, proliferation, invasive and metastatic features of cancer cells.…”
Section: Introductionmentioning
confidence: 67%
“…It suggested that SLC3A2, SLC7A11 held the highest diagnostic value. In LUAD patients, previous studies have suggested that NDUSF1 was associated with invasion and cognitive impairment, and was a potential therapeutic target [38,39]. High expression of LRPPRC was associated to poor prognosis and down-regulation of LRPPRC could meliorate drug resistance of LUAC [40].…”
Section: Discussionmentioning
confidence: 99%
“…MRPS15 is significantly upregulated in epithelial breast cells and tissues [10]. Mitochondrial COX1 is expressed abnormally in multiple cancers [11][12][13]. Many cancer-relevant communication signaling pathways are linked to mitochondrial proteins.…”
Section: Introductionmentioning
confidence: 99%